Effect of Duration on Variations in Bed Topography and Water Surface Profile in a Meandering Channel - Nargess Moghaddassi; Seyed Habib Musavi-Jahromi; Amir Khosrojerdi (Journal of Hydraulic Structures, 2021)
In this study, variations in water surface profile and bed topography along a meandering path were examined under different experiment durations. Although several studies have been conducted on sediment and scour in open channels, addressing temporal variations in meandering channels requires independent, merely experimental research. In this regard, a meandering laboratory flume consisting of two consecutive 180-degree bends was used in this study. The test was conducted under clear water conditions and in 6 different durations equal to 0.2, 0.4, 0.5, 0.6, 0.8, and 1 times the equilibrium time (240 minutes). Results indicated that at the downstream bend, lengthening the test time from 0.2 to 0.4, 0.5, 0.6, 0.8, and 1 times the equilibrium time added to the maximum scour by 70, 100, 115, 120, and 165%, and also increased the maximum sedimentation by 30, 25, 45, 45, and 45%, respectively. Moreover, with a comparison made between the average transversal water surface profile for 0, 120, and 240-minute duration tests, it was observed that when these transversal profiles were displaced from 45 degrees to 90, 135, and 180 degrees, the water surface at the inner bank was lowered by 2, 5, and 7% and that at the outer bank decreased by 2, 6, and 12%, respectively.